Quantifying the severity of hurricanes on extinction probabilities of a primate population: Insights into "Island" extirpations. Issue 7 (2nd April 2015) - Ameca y Juárez, Eric I.; Ellis, Edward A.; Rodríguez‐Luna, Ernesto
<x xml:space="preserve">Abstract</x> Long‐term studies quantifying impacts of hurricane activity on growth and trajectory of primate populations are rare. Using a 14‐year monitored population of Alouatta palliata mexicana as a study system, we developed a modeling framework to assess the relative contribution of hurricane disturbance and two types of human impacts, habitat loss, and hunting, on quasi‐extinction risk. We found that the scenario with the highest level of disturbance generated a 21% increase in quasi‐extinction risk by 40 years compared to scenarios of intermediate disturbance, and around 67% increase relative to that found in low disturbance scenarios. We also found that the probability of reaching quasi‐extinction due to human disturbance alone was below 1% by 40 years, although such scenarios reduced population size by 70%, whereas the risk of quasi‐extinction ranged between 3% and 65% for different scenarios of hurricane severity alone, in absence of human impacts. Our analysis moreover found that the quasi‐extinction risk driven by hunting and hurricane disturbance was significantly lower than the quasi‐extinction risk posed by human‐driven habitat loss and hurricane disturbance. These models suggest that hurricane disturbance has the potential to exceed the risk posed by human impacts, and, in particular, to substantially increase the speed of the extinction vortex driven by habitat loss relative to that driven by hunting. Early mitigation of habitat loss constituted the best method for reducing quasi‐extinction risk: the earlier habitat loss is halted, the less vulnerable the population becomes to hurricane disturbance. By using a well‐studied population of A. p. mexicana, we help understand the demographic impacts that extreme environmental disturbance can trigger on isolated populations of taxa already endangered in other systems where long‐term demographic data are not available. For those experiencing heavy anthropogenic pressure and lacking sufficiently evolved coping strategies against unpredictable environmental disturbance, the risk of population extinction can be exacerbated. Am. J. Primatol. 77:786–800, 2015. © 2015 Wiley Periodicals, Inc.